Pair-epitopes vaccination: enabling offspring vaccination in the presence of maternal antibodies. Issue 6 (2nd November 2017) - Pitcovski, Jacob; Pitcovski, Eli; Goldenberg, Dana; Shahar, Ehud
ABSTRACT: Maternally derived antibodies (MDAs) are critical for offspring protection during the first days of life. However, due to their short half-life (3–5 days), MDA levels decline rapidly and by 8–15 days post-hatch drop to below protective levels. In addition, MDAs against a specific pathogen often impede the efficient protective immune response to that pathogen by the new-born following vaccination. The combination of these two phenomena generates a gap in protection in the period between loss of MDA protection and development of vaccine-induced protective antibodies. Herein, a concept is presented that might enable effective vaccination of 1-day-old progeny in the presence of MDAs. The idea is to vaccinate mothers and their progeny with different neutralizing epitopes of the same pathogen. This will allow an effective immune response of the progeny towards neutralizing epitopes while retaining MDA protection until high levels of self-antibodies are produced. This concept is valid for various avian viruses that express two neutralizing proteins or have numerous neutralizing epitopes on the same protein, for example, Newcastle disease virus and infectious bursal disease virus, respectively. These may be used as protein subunit vaccines or live vaccines carried by a vector. This vaccination concept may overcome the gap in protection that occurs when MDAs decrease while self-immunity is still partial, to provide continuous protection at a young age.